Chronic Pain Personification Following Child Abuse: The Imprinted Experience of Child Abuse in Later Chronic Pain - Tsur, Noga (Journal of interpersonal violence, 2022)
Child abuse has been shown to increase the risk for chronic pain. The illness personification theory implies that individuals tend to ascribe humanlike characteristics to chronic pain, and that this personification is embedded in the way they cope with their chronic condition. Recent findings demonstrate that individuals who experienced interpersonal violence tend to personify chronic pain in a way that resonates with past abusive experience. Although findings prevail to the link between trauma and the experience of the body, the personification of chronic pain among individuals who experienced child abuse has not been examined before. This article includes two studies that tested whether child abuse is implicated in abusive chronic pain personification in a young adult female sample (Study 1) and among females who experienced child abuse (Study 2). In both studies, self-report measures of child abuse, posttraumatic stress (PTS) symptoms, complex posttraumatic symptoms (disturbances of self-organization [DSO]), and abusive chronic pain personification were administered. Structural equation modeling was utilized to assess the hypotheses. The findings of the two studies showed a significant association between child abuse and pain personification. Whereas PTS symptoms did not mediate this link (Study 1), DSO symptoms mediated this association (Study 2). The findings of these studies support the understanding that the experience of interpersonal violence is engraved in the experience of the body, as reflected in abusive chronic pain personification. Disturbances in self-organization seem to underlie this process, thus pertaining to the link between the experience of the body, self, and interpersonal trauma.